A new proposal for simplified design of buried steel pipes crossing active faults. - Takada, Shiro
Simplified design methods for obtaining the maximum strain in pipelines crossing active faults proposed by Newmark, Kennedy and Wang have not considered the section deformation of the pipe. In this study, a new simplified method is developed for obtaining the maximum strain in steel pipes crossing faults considering non-linearity of material and geometry of pipe section. It is assumed that the pipe will bend near the fault and the geometry of pipe in the longitudinal direction will change according to a bent deformation. On the other hand, the relation between maximum strain and bent angle has been obtained using a beam shell hybrid FEM for different pipe fault conditions. The developed method can be used for calculating the maximum strains for fault crossing steel pipes with different angles of crossing both in tension and compression, by considering the deformation of the pipe cross section.
Keywords: Simplified method; Steel pipe; 3D shell model; Fault crossing; Bending angle; Maximum strain